The Importance of Acknowledging the Sociocultural Context in Ethical Assessments of Generative AI Tools for Clinical Summarization. - Collins, Benjamin Xavier (American Journal of Bioethics, 2026)
This article examines the ethical considerations surrounding artificial intelligence (AI)-supported clinical summarization tools, emphasizing the influence of sociocultural context on stakeholder values and potential value conflicts. It highlights the criminalization of health data—such as information related to substance use, abortion, transgender care, and immigration status—as a critical ethical concern, noting that sociocultural and legal variations by location affect risks to patients and clinicians. The study also discusses how ambient AI scribe functionalities, which capture voice data during clinical encounters, introduce additional ethical complexities, including the need for patient disclosure about AI involvement. Furthermore, the article identifies various sociocultural factors—such as healthcare coverage models, healthcare worker roles, communication styles, and levels of trust in healthcare and AI—that shape the ethical analysis of AI tools in healthcare across different regions.